Asymptotic method based on Maslov's theory for the focusing of 3D elliptical lens placed in chiral medium. Issue 10 (2nd July 2016) - Rahim, Tariq; Ullah, Naveed; Ibrahim, Muhammad; Shah, Murad Ali; Xu, Jiadong
Abstract : The high-frequency field expressions for the refracted waves from the dielectric 3D elliptical lens embedded in homogeneous and reciprocal chiral medium around the focal region are derived using an asymptotic method based on Maslov's theory. Ray-based Geometric Optics (GO) technique was initially used to derive the expressions for the electrical field intensities for both left circular polarized and right circular polarized waves which are inherited in the chiral medium. However, GO method is not applicable at the focal points due to the shrinking of ray volume at these points which causes unreal singularities. Therefore, an asymptotic method based on Maslov's theory is applied to derive the fields at the focal points. Moreover, the effect of chirality parameter on the behavior of focal points electric field intensities are indicated using the line plots obtained from the numerical solution of the derived equations using MATLAB software. A special case of the dielectric 3D elliptical lens placed in achiral medium is also discussed using the expressions.